Environmental Impact of Sewage Discharge on Shallow Embayment and Mapping of Microbial Indicators - Alkhalidi, Mohamad A.; Al-Nasser, Zahraa H.; Al-Sarawi, Hanan A. (Frontiers in Environmental Science, 2022)
Marine pollution in shallow embayments is hazardous to human and marine health. This research investigates the environmental impact of sewage discharge from coastal outfalls on the semi-enclosed-shallow Doha Bay. Such a study highlights the impact of environmental stressors on the health of such bays. Also, the study assesses the spreading of the pollutant relative to the location of the pollution source. The bay is susceptible to sewage discharge as it is featured slow tidal currents leading to increased pollution concentrations within its basin. The concentrations and distributions of microbial water quality indicators (E.coli, fecal Coliform, and fecal streptococci) were investigated parallel with physical and chemical water quality parameters. Water samples were collected from the outfalls and within Doha Bay for four months. The results show that the concentrations of discharged Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Total Organic Carbon (COD), Nitrites (NO_2^-) and ammonia (NH3) has exceeded Kuwait Environment Public Authority (KEPA) maximum limits, specifically from the outfalls J3 and J4. In addition, the microbiological parameters were significantly breaching KEPA's guidelines. The maximum fecal coliform concentration was 3.5×105, 2.4×104, and 5.4×103 CFU/100 ml, E.coli concentration was 2.2×105, 1.2×104, and 2.6×103 CFU/100 ml, fecal streptococci concentration was 7.25×102, 4.4×102, and 44 CFU/100 ml, at outfalls J3, J4, and J5, respectively, indicating high microbial pollution. The fecal Coliform near J3 exceeds the allowable limits of KEPA by more than 600 times. Laboratory results were mapped to assess the microbial indicators within the bay. Spatially, the concentration of pollutants varies and correlates proportionally with the locations of the outfalls. The highly affected area is near outfall J3: a shallow, closed area with minimal water circulation and maximum sewage discharge. Offshore locations show lower pollution concentrations, and the pollutant concentrations were highest in January 2019 and February 2019. Continuing to discharge pollutants through coastal outfalls to regions such as Doha Bay will lead to long-term consequences, including eco-social, ecological, and adverse health impacts that are complex to be treated. Therefore, the bay needs an independent, comprehensive, and reliable monitoring program to measure the environmental indicators continuously.